Enantioselective total synthesis of (-)-xialenon A. - Hodgson, D; Galano, J; Christlieb, M (2002)
The first total synthesis of (-)-xialenon A (1) via conjugate allylation of a 1,5-cyclooctadiene-derived bicyclo[3.3.0]octenone 3 and an alpha'-hydroxylation on the more hinderd face of enone 9 using hypervalent iodine chemistry, is described.